2016
DOI: 10.1089/thy.2016.0055
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin Levels Are Associated with Cardiometabolic Risk Factors in Euthyroid Adolescents

Abstract: Background: Increased thyrotropin (TSH) levels and free triiodothyronine to free thyroxine (fT3:fT4) ratios, even within the euthyroid range, have been associated with cardiometabolic risk factors in adults but are less characterized in youth. This study sought to determine relations between TSH, thyroid hormones, and cardiometabolic risk factors in euthyroid adolescents. Methods: Data were extracted from the United States National Health and Nutrition Examination Survey, 2007-2010, for univariate and multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 45 publications
4
25
0
Order By: Relevance
“…The higher the TSH level, the higher the diastolic blood pressure. Similar observations were made by Lee et al, who reported higher systolic blood pressure in adolescents aged 12-19 with elevated TSH levels [11]. The relationship between the thyroid hormone level and the value of the arterial pressure, confirmed in both studies, is of great clinical significance.…”
Section: Discussionsupporting
confidence: 88%
“…The higher the TSH level, the higher the diastolic blood pressure. Similar observations were made by Lee et al, who reported higher systolic blood pressure in adolescents aged 12-19 with elevated TSH levels [11]. The relationship between the thyroid hormone level and the value of the arterial pressure, confirmed in both studies, is of great clinical significance.…”
Section: Discussionsupporting
confidence: 88%
“…Thyroid hormone take part in regulating basal metabolism, thermogenesis and also play an important role in glucose-lipid metabolism [12]. Previous study has shown that FT3/FT4 ratio negatively associated with HDL-C and positively with TG in euthyroid adolescents [13]. In this study, we found that FT3 was significantly negatively with HDL-C in all obesity.…”
Section: Discussionsupporting
confidence: 57%
“…About glucose metabolism, TSH is positively correlated with 2 h-glucose and HOMA-IR in youth with euthyroid [13]. FT3/FT4 ratio was positively with fasting and 2 h-glucose, fasting insulin and HOMA-IR [13].…”
Section: Discussionmentioning
confidence: 92%
“…37,38 Low thyroid hormone levels also increase systemic vascular resistance and induce endothelial dysfunction by reducing nitric oxide availability. [37][38][39] Previous studies, [5][6][7]40 including those using NHANES data, 5,7 reported that low thyroid function even within the normal range is associated with metabolic syndrome owing to an increase in insulin resistance and might contribute to the progression of atherosclerosis and CVD risk. 41 While the exact underlying mechanisms are still unclear, these biological mechanisms support our finding that CVD partially mediates the association of higher TSH concentrations with death.…”
Section: Discussionmentioning
confidence: 99%